Kualitas Pelayanan Staf Front Office Hotel Di Bali - Indah Kusumarini (JURNAL BISNIS HOSPITALITI, 2021)
This reseach was conducted by using the theory of service quality dimensions from Zeithaml-Parasuraman-Berry (1996). Data obtained by distributing 100 questionnaires to Japanese tourists on August 2019. The variable created refers to the role of the front office clerk from Bagiono (2012). Based on SPSS calculations, the accuracy of this research model is 73% at an error rate of 5%. From the results of data processing it is known that the average value of the service quality of front office staff at star hotels in Bali is 4.11 (good). But there are still indicators that are not good, that is, an indicator of Japanese language ability, with an average value of 3.23. Based on the results of exploratory factor analysis of 31 variables, found 7 factors forming the quality of front office staff services,  1) responsiveness with a value (13,916), 2) empathy (2,355), 3) reliability (1,513), 4) tangible (1,486) , 5) assurance (1.29), 6) friendly (1,220), and 7) communication (1,140).  The biggest factor influencing the satisfaction of Japanese tourists towards the quality of front office staff services is the responsiveness factor while the lowest factor is the communication factor.